Everyday politics, social practices and movement networks: daily life in Barcelona's social centres1. (18th January 2015) - Yates, Luke
Abstract The relations between everyday life and political participation are of interest for much contemporary social science. Yet studies of social movement protest still pay disproportionate attention to moments of mobilization, and to movements with clear organizational boundaries, tactics and goals. Exceptions have explored collective identity, 'free spaces' and prefigurative politics, but such processes are framed as important only in accounting for movements in abeyance, or in explaining movement persistence. This article focuses on the social practices taking place in and around social movement spaces, showing that political meanings, knowledge and alternative forms of social organization are continually being developed and cultivated. Social centres in Barcelona, Spain, autonomous political spaces hosting cultural and educational events, protest campaigns and alternative living arrangements, are used as empirical case studies. Daily practices of food provisioning, distributing space and dividing labour are politicized and politicizing as they unfold and develop over time and through diverse networks around social centres. Following Melucci, such latent processes set the conditions for social movements and mobilization to occur. However, they not only underpin mobilization, but are themselves politically expressive and prefigurative, with multiple layers of latency and visibility identifiable in performances of practices. The variety of political forms – adversarial, expressive, theoretical, and routinized everyday practices, allow diverse identities, materialities and meanings to overlap in movement spaces, and help explain networks of mutual support between loosely knit networks of activists and non‐activists. An approach which focuses on practices and networks rather than mobilization and collective actors, it is argued, helps show how everyday life and political protest are mutually constitutive.